A lumped specific heat capacity approach for predicting the non-stationary thermal profile of coffee during roasting - Basile, M. (Array, 2009)
Summary: Coffee undergoes numerous and relevant chemical and physical changes during roasting. These modifications lead to the development of those typical organoleptic properties of coffee, on which the acceptability of the product depends. The roasting process therefore, plays a central role within the coffee’s technological cycle. This crucial character of roasting has contributed to encouraging the continuous progress of the roasting industry incorporating the necessary scientific and technological research. However, due to the geometrical complexity and transformations undergone by coffee during roasting, the relationship between the heating mode and the material properties of coffee on the one hand and the non-stationary temperature profile within the bean on the other, are still far from being fully understood. In this presented work, a dynamic model is proposed for predicting the non-stationary thermal profile of coffee during roasting. The model is based on the assumption that the thermal effects occurring within the bean during roasting, such as moisture evaporation, can be approximately encompassed within a lumped together specific heat parameter. Using this hypothesis, it is possible to develop a mathematical model, which is quite simple in structure but still able to describe the two most important technological aspects, i.e. the evolution over time of the beans’ average temperature and internal thermal gradient